2020
DOI: 10.1001/jamacardio.2020.2871
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Quality of Internet-Based Cardiopulmonary Resuscitation Training Films Featuring Women Experiencing Cardiac Arrest

Abstract: Despite efforts to reduce disparities in cardiopulmonary resuscitation (CPR) provision, men are more likely than women to receive bystander CPR worldwide. 1,2 Women have worse outcomes following out-of-hospital cardiac arrest than men. [1][2][3] In the Resuscitation Outcomes Consortium registry, men had a 29% increased probability of survival to discharge compared with women. 1 Bystanders report common themes behind hesitation to perform CPR on women. Bystanders are less likely to remove clothing and place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These YouTube videos were selected by the course instructor for this study, as they covered the same content as the screencast video by the instructor and the contents included the key aspects of CPR education that are reported in the literature, namely: (1) assessing scene safety, (2) checking victim responsiveness, (3) initiating contact with emergency medical services, (4) proper hand positioning for CPR, (5) accurate compression rate (100–120 per minute), and (6) appropriate chest compression depth (2–2.5 inches) [ 19 ]. The YouTube videos were not modified for the purpose of the course.…”
Section: Methodsmentioning
confidence: 99%
“…These YouTube videos were selected by the course instructor for this study, as they covered the same content as the screencast video by the instructor and the contents included the key aspects of CPR education that are reported in the literature, namely: (1) assessing scene safety, (2) checking victim responsiveness, (3) initiating contact with emergency medical services, (4) proper hand positioning for CPR, (5) accurate compression rate (100–120 per minute), and (6) appropriate chest compression depth (2–2.5 inches) [ 19 ]. The YouTube videos were not modified for the purpose of the course.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20] A recent study observed that there is a scarcity of female-specific CPR instructional videos available on the internet. 21 To our knowledge, there has been no systematic analysis comparing videos about Hands-only CPR based on the gender of the recipient. Given the importance and misconceptions about it, this type of analysis would be a valuable next step in developing interventions.…”
Section: Introductionmentioning
confidence: 99%